Mapping the geological landscape of NW bay of Navarino through time - Καϊμακάμη, Μαρία (Πανεπιστήμιο Πελοποννήσου, 2024)
This study presents the geological landscape in the western bay of Navarino over time by creating maps. The maps aim to depict the relationship between the geological landscape and the human presence in the specific area. After field survey, the use of Geographic Information System (GIS) and the optical microscope LED, maps were created that identified the geological landscape and presented the archaeological data. The result was that in three elevated areas and around them, on the peninsula of Coryphasium, the hills of Prophitis Ilias and Koukouras, which were mainly made of limestone, more archaeological findings found mostly ceramics sometimes together with walls and large limestone rocks compared with around or inside the lagoon and the cultivated lands. This fact is related to the human habitation in this area and if it was affected by the geological landscape over the centuries. For this reason, a discussion was developed to understand better why the findings were found in this way. Finally, a first picture of the correlation of the long-term habitation and the geological landscape was understood and more research needs to be done for safer results about the human presence.
Χαρτογράφηση του γεωλογικού τοπίου του ΒΔ κόλπου του Ναβαρίνου μέσα στο χρόνο
Keywords: Κόλπος Ναυαρίνου (Ελλάδα) -- Χάρτες, Εικονογραφικά; Αρχαιολογία -- Γεωγραφικά συστήματα πληροφοριών -- Ελλάδα -- Μεσσηνία; Γεωλογία -- Ελλάδα -- Μεσσηνία; Ανθρώπινη γεωγραφία -- Ελλάδα -- Μεσσηνία; Ελλάδα -- Αρχαιότητες -- Χάρτες; Geographic Information System (GIS); Optical Microscope LED; Navarino; Pylos; Geological Landscape; Human Habitation; Field Survey; Rocks; Maps; Archaeological Findings; Γεωγραφικό Σύστημα Πληροφοριών (GIS); Οπτικό Μικροσκόπιο LED; Ναβαρίνο; Πύλος; Γεωλογικό Τοπίο; Ανθρώπινη Κατοίκηση; Έρευνα Πεδίου; Πετρώματα; Χάρτες; Αρχαιολογικά Ευρήματα